2008
DOI: 10.1074/jbc.m806817200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Receptor Signaling by Relaxin A Chain Motifs

Abstract: Relaxin peptides are important hormones for the regulation of reproductive tissue remodeling and the renal cardiovascular system during pregnancy. Recent studies demonstrated that two of the seven human relaxin family peptides, relaxin H2 (RLN2) and INSL3, signal exclusively through leucine-rich repeat-containing G protein-coupled receptors, LGR7 and LGR8. Although it was well characterized that an RXXXRXXI motif at the RLN2 B chain confers receptor activation activity, it is not clear what roles RLN2 A chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…This finding is consistent with studies by Park et al (18), which suggest that Tyr A16 and Lys A17 are important for the H2 relaxin interaction with RXFP1. However, the nature of such an interaction is unclear as no drop in affinity for RXFP1 was seen when either of these residues were mutated by Ala but only when replaced by Gly (18), which may suggest a secondary effect related to structural changes. Clearly, further mutational studies targeting the midto C-terminal part of H2 relaxin A-chain are required to shed light on its role in receptor activation, in particular for the development of a highly sought after high affinity RXFP1 antagonist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding is consistent with studies by Park et al (18), which suggest that Tyr A16 and Lys A17 are important for the H2 relaxin interaction with RXFP1. However, the nature of such an interaction is unclear as no drop in affinity for RXFP1 was seen when either of these residues were mutated by Ala but only when replaced by Gly (18), which may suggest a secondary effect related to structural changes. Clearly, further mutational studies targeting the midto C-terminal part of H2 relaxin A-chain are required to shed light on its role in receptor activation, in particular for the development of a highly sought after high affinity RXFP1 antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…1). These included the following: four B-chain N-terminal truncated analogues (H2-(B3-29), H2-(B5-29), H2-(B7-29), and H2-(B9 -29)), six B-chain C-terminal truncated analogues (H2-(B1-28), H2-(B1-27), H2-(B1-26), H2-(B1-25), H2-(B1-24), and H2-(B1-23)), four B-chain Nand C-terminal truncated analogues (H2-(B7-25), H2-(B7-24), H2-(B8 -25), and H2-(B8 -24)), and six A-and B-chain truncated analogues (H2-(A2-24)(B7-24), H2-(A3-24)(B7-24), H2-(A4 -24)(B7-24), H2-(A5-24)(B7-24), H2-(A7-24)(B7-24), and H2-(A9 -24) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)). All of these H2 analogues were amidated at the C termini of both the A-and B-chains.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Binding of relaxins to RXFP1 is mediated via high-affinity binding to extracellular domain of RXFP1 and an additional binding site in the transmembrane (TM) exoloops ( Sherwood, 2004 ). A recent study has shown that specific residues in the center of the H2 relaxin A-chain are necessary for ligand activity at RXFP1 ( Park et al, 2008 ). Importantly, modeling of the ligand–receptor interaction for different RXFP receptors suggests that once the B-chains of the ligands are bound to the primary binding site in a large ectodomain with 10 leucine-rich repeats (LRRs) that the A-chain is presented in a favorable orientation for interaction with the TM exoloops ( Hartley et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%